Which function is the inverse of f(x) = 2x + 3?
We will use the concept of transposition to find the inverse function.
Answer : f-1(x) = (x - 3) / 2
Let's see how we will use the concept of transposition to find the inverse function.
We have been given a function f(x) = 2x + 3
For finding inverse we will solve y = 2x + 3 to write x as a function of y and that will be our inverse function.
Therefore, we have
y = 2x + 3
y - 3 = 2x
(y - 3) / 2 = x
Now substituting x in place of y and f-1(x) in place of x, we get , f-1(x) = (x - 3) / 2
You can use the inverse function formula to verify the result.